2022
DOI: 10.3390/ijtm2030033
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin in Cancer: Mechanisms and Therapeutic Targets

Abstract: Despite significant advances in the understanding of cancer biology, cancer is still a leading cause of death worldwide. Expression of the tumor microenvironment component, osteopontin, in tumor tissues, plasma, and serum, has been shown to be associated with a poor prognosis and survival rate in various human cancers. Recent studies suggest that osteopontin drives tumor development and aggressiveness using various strategies. In this review, we first provide an overview of how osteopontin promotes tumor progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 230 publications
0
30
0
Order By: Relevance
“…SPP1 protein is produced in multiple organs throughout the body in physiological and disease conditions, and osteoblasts, fibroblasts, activated macrophages in healing wounds, and dendritic cells are known to be sources of SPP1 [ 6 , 9 ]. Many reports suggested that the levels of circulating SPP1 and/or an increased level of SPP1 expression in tumor cells are correlated with a poor prognosis in NSCLC [ 7 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPP1 protein is produced in multiple organs throughout the body in physiological and disease conditions, and osteoblasts, fibroblasts, activated macrophages in healing wounds, and dendritic cells are known to be sources of SPP1 [ 6 , 9 ]. Many reports suggested that the levels of circulating SPP1 and/or an increased level of SPP1 expression in tumor cells are correlated with a poor prognosis in NSCLC [ 7 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteopontin, also called secreted phosphoprotein 1 (SPP1), is a multifunctional secreted phosphorylated glycoprotein that has an arginine-glycine-aspartate-containing (RGD-containing) domain, which was first identified in bone tissue as a major sialoprotein that modulates bone formation and remodeling. The RGD site of SPP1 can bind to multiple integrins, such as α v β 3 , α v β 5 , α v β 1 , and α 5 β 1 , and to certain variant forms of CD44 [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteopontin plays an important role in tumor progression, promoting, among other things, tumor growth and tumor cell invasion [ 178 ]. Increased expression of osteopontin was found in human bladder cancer cell lines [ 179 ].…”
Section: The Association Of Adipokines With Sleep Disorders and Cancermentioning
confidence: 99%
“…Also called SPP-1 (secreted phosphoprotein 1), BSP-I (Bone Sialoprotein I), nephropontin, 2AR and ETA1 (early T-lymphocyte activation 1), OPN is expressed physiologically and pathologically by various types of cells, reflecting its functional roles in bones, the immune system, and the central nervous system [ 3 , 4 ]. Furthermore, it has been implicated in the pathophysiology of diverse diseases, including cancer, diabetes and autoimmune and neurodegenerative conditions, as well as cardiovascular disease [ 5 , 6 , 7 , 8 , 9 ]. Alternative splicing and alternative translation produce OPN transcripts that encode protein isoforms that can be located intracellularly and extracellularly, while post-translational modification, such as proteolytic processing, phosphorylation and glycosylation, further enriches the complexity of the osteopontin protein isoforms [ 8 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, OPN expression in the tumour microenvironment is associated with various aspects of progression, including promotion of cell migration, invasion and metastasis, fostering proliferation and tumour growth, enabling tumour cell survival, chemoresistance and stemness properties, induction of epithelial mesenchymal transition, stimulation of angiogenesis and the activation of CAFs, as well as the creation of a tumour-promoting immunosuppressive microenvironment [ 22 , 30 , 31 ]. In view of this, OPN is receiving increasing interest as a therapeutic target, and a number of approaches are currently in preclinical development, including several antibodies that interfere with the binding of OPN to its receptors, which have shown promise in animal tumour models [ 7 , 32 , 33 , 34 ] and other pathological conditions [ 35 , 36 ]. With the recent rapid advances in the use of immune checkpoint inhibitors to treat cancer, the therapeutic targeting of OPN has particularly come to the fore in view of findings that OPN can bypass anti-PD1 immunotherapy [ 33 , 37 ].…”
Section: Introductionmentioning
confidence: 99%